SIW slot antennas utilized for 60‐GHz channel characterization. Issue 6 (June 2015) - Mikulasek, Tomas; Lacik, Jaroslav; Raida, Zbynek
ABSTRACT: In this work, substrate integrated waveguide (SIW) slot antennas are proposed for 60‐GHz channel characterization. The antennas consist of a group of three longitudinal slots placed in one or both broad walls of an SIW. Depending on the placement of the slot group, the SIW slot antenna achieves a directional or omnidirectional radiation pattern. An SIW slot antenna is naturally a narrow‐band structure; however, using different self‐resonant frequencies of the slots in the group ensures a wide operation frequency band (55–65 GHz). In this way, new utilization possibilities of the SIW slot antennas are proposed. The antenna design is performed in the full‐wave electromagnetic solver ANSYS High Frequency Structure Simulator (HFSS) and verified by measurement. Experimental results validate good impedance matching and a directional or omnidirectional radiation pattern of the fabricated antennas. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1365–1370, 2015